Mengembangkan Bakat Menulis Siswa SMK: Strategi Inovatif Untuk Menjadi Penulis Cerpen Yang Handal - Nabila Salwa (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the ways to develop short story writing skills of vocational high school students, the factors causing the lack of such skills, innovative and effective strategies to be applied, the effectiveness of applying such strategies, and the benefits that students can obtain in developing their short story writing skills. The research method used is qualitative research with data collection techniques through interviews, observations, and literature review. The results show that factors such as lack of motivation, limited vocabulary, and lack of understanding of short story structure can cause the lack of short story writing skills among vocational high school students. Innovative and effective strategies that can be applied include the use of visual and audio media, vocabulary development, and short story writing techniques application. The implementation of these strategies is effective in improving short story writing skills of vocational high school students and can provide benefits in developing critical thinking skills, creativity, as well as improving language and literacy skills of students.